Simulated Microgravity Conditions and Carbon Ion Irradiation Induce Spermatogenic Cell Apoptosis and Sperm DNA Damage - LI, Hong Yan; ZHANG, Hong; MIAO, Guo Ying; XIE, Yi; SUN, Chao; DI, Cui Xia; LIU, Yang; LIU, Yuan Yuan; ZHANG, Xin; MA, Xiao Fei; XU, Shuai; GAN, Lu; et al. (Biomedical and environmental sciences, 2013)
Objective To investigate the effect of simulated microgravity and carbon ion irradiation （CIR） on spermatogenic cell apoptosis and sperm DNA damage to the testis of male Swiss Webster mice, and assess the risk associated with space environment. Methods Sperm DNA damage indicated by DNA fragmentation index （DFI） and high DNA stainability （HDS） was measured by sperm chromatin structure assay （SCSA）. Apoptosis of spermatogenic cells was detected by annexin V-propidium iodide assay. Bax （the expression levels of p53） and proliferating cell nuclear antigen （PCNAI were measured by immunoblotting; p53 and PCNA were located by immunohistology. Results HDS, DFI, apoptosis index, and the expression levels of p53 and Bax were detected to be significantly higher in the experimental groups （P〈0.05） compared with those in the control group, however, the PCNA expression varied to a certain degree, p53- and PCNA- positive expression were detected in each group, mainly in relation to the spermatogonic cells and spermatocytes. Conclusion The findings of the present study demonstrated that simulated microgravity and CIR can induce spermatogenic cell apoptosis and sperm DNA damage. Sperm DNA damage may be one of the underlying mechanisms behind male fertility decline under space environment. These findings may provide a scientific basis for protectint~ astronauts and space traveler＇s health and safety.